Formação continuada em serviço: a prática do pedagogo no ensino da matemática nos anos iniciais ancorado nas metodologias ativas e recursos tecnológicos - Scolaro, Joelma Kominkiewicz (2025)
This study is aimed at analyzing how the effects of applying a didactic sequence, in continuing in-service education, with the support of active methodologies and technological resources, have influenced the actions of the pedagogue teacher, for teaching mathematics in the early years of elementary school. Works by Freire (1996) and Tardif (2008), which address teacher training in general, and a specific study on the training of pedagogues, based on scholars who contributed to the historical evolution of the area in Brazil, were used as framework. The research also sought to portray Pedagogy courses in contemporary times, based on the DCNs (Diretrizes Curriculares Nacionais – National Curriculum Guidelines) (2001/2024) and data from INEP (Instituto Nacional de Pesquisas Educacionais – National Institute of Educational Research), in addition to exploring in-service continuing education and the preparation of pedagogues for teaching mathematics in early years. The framework also draws on theories about the use of technological resources in education and on active methodologies that support this research, which is aimed at solving the identified problem, marked by the predominance of conventional teaching methodologies and conservative practices, widely observed in the process of teaching mathematics in early years. Although there are training courses in this area, many professionals cannot access them, either due to a lack of familiarity with technologies or because they do not know where to look for such information. The problem gave rise to the question: how to promote the continuing in-service training of pedagogue teachers, through innovative practices, aimed at enhancing pedagogical skills for teaching mathematics in early years, based on active methodologies and the use of digital technologies? Aligned with the theoretical framework and teaching practice in the Pedagogy course, the viability of elaborating an Educational Product in the form of a didactic sequence, with the theme “Training teachers with active and technological approaches to teaching mathematics”, was identified. This product was structured in eight hybrid meetings, with three face-to-face hours and two online hours, totaling 40 hours of training. Methodologically speaking, the research is qualitative and applied in nature, explanatory, with the adoption of action research. The application was carried out as continuing training for pedagogue teachers in service in the state education network of Santa Catarina, belonging to the CRE (Coordenadoria Regional de Educação – Regional Coordination of Education) of Campos Novos – SC. Data collection instruments included questionnaires, productions, interviews, logbook, recordings and records of meetings. Data analysis was carried out using Content Analysis (CA), with the aim of interpreting responses and records, identifying patterns and meanings that contribute to the reflection and improvement of educational practices, through the following categories of analysis: “Prior Knowledge”, “Active Methodologies in Teaching Mathematics mediated by Technological Resources”; and “In-Service Teacher Training”. The analysis allowed us to assess the acceptance of the practical activities that were proposed, identify patterns of behavior and demonstrate the learning of the teachers in training, with practical application in the teaching process. The material produced will be available for free access and use on the portal of the Postgraduate Program in Science and Mathematics Teaching at the University of Passo Fundo http://www.upf.br/ppgecm and on the EduCapes website http://educapes.capes.gov.br/handle/capes/1001009.